DEKONSTRUKSI BIAS GENDER DALAM TAFSIR AL-QUR'AN: STUDI TENTANG AYAT-AYAT BIDADARI OLEH MUHAMMAD QURAISH SHIHAB - Siti Abidah Subkiyyah; Mokhamad Sukron (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2025)
This study specifically aims to examine three primary aspects of Muhammad Quraish Shihab’s exegesis on the verses concerning ḥūr ‘ain: first, how his interpretation balances literal and symbolic meanings in elucidating the concept of bidadari (heavenly maidens); second, how his tafsir critiques and revises the patriarchal gender biases embedded in classical interpretations; and third, how his interpretation contextualizes the understanding of the bidadari verses within the social and spiritual realities of modern Muslim communities. With this focus, the research seeks to fill an academic gap that has hitherto insufficiently addressed modern exegetical approaches which not only preserve the textual authenticity of the Qur’an but also accommodate the demands of contemporary times and gender justice. Employing qualitative methods and content analysis, this study provides a comprehensive overview of the hermeneutical strategies employed by Quraish Shihab in Tafsir Al-Misbah, while opening an academic discourse on the impact of his interpretation on gender discourse within Islam and its reception in contemporary intellectual circles. The findings affirm that Quraish Shihab’s tafsir endeavors to redefine the eschatological narrative of ultimate bliss in a more inclusive and progressive manner, positioning the bidadari as a universal symbol that transcends the traditionally reductive and patriarchal meanings. This approach enables readers to situate these verses within a richer and more relevant theological framework, while significantly contributing to the development of contemporary tafsir characterized by dialogical and critical engagement. Consequently, this interpretation plays a pivotal role in broadening gender perspectives within Islamic studies, opening avenues for reinterpretations of religious texts that embrace gender equality and the pluralistic experiences of Muslim communities. The study also highlights the necessity for continued scholarship that integrates exegetical inquiry with social and gender analyses, ensuring that tafsir serves not merely as textual exegesis but as a vehicle for progressive social transformation.